2010
DOI: 10.1016/j.crte.2009.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Univariate modelling of summer-monsoon rainfall time series: Comparison between ARIMA and ARNN

Abstract: The present article reports studies to develop a univariate model to forecast the summer monsoon (June-August) rainfall over India. Based on the data pertaining to the period 1871-1999, the trend and stationarity within the time series have been investigated. After revealing the randomness and non-stationarity within the time series, the autoregressive integrated moving average (ARIMA) models have been attempted and the ARIMA(0,1,1) has been identified as a suitable representative model. Consequently, an autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 65 publications
3
38
0
1
Order By: Relevance
“…In general, the foregoing results bear comparison with results of some early studies (e.g. Chattopadhyay and Chattopadhyay, 2010;Chattopadhyay et al, 2011), which confirmed that ARIMA forecasting models are suitable for hydrological data. Furthermore, detailed studies on ARIMA and artificial neural network (ANN) modelling (e.g.…”
Section: Arima Modellingsupporting
confidence: 81%
“…In general, the foregoing results bear comparison with results of some early studies (e.g. Chattopadhyay and Chattopadhyay, 2010;Chattopadhyay et al, 2011), which confirmed that ARIMA forecasting models are suitable for hydrological data. Furthermore, detailed studies on ARIMA and artificial neural network (ANN) modelling (e.g.…”
Section: Arima Modellingsupporting
confidence: 81%
“…This study investigated the applicability of the adaptive neuro-fuzzy inference system (ANFIS) and the autoregressive integrated moving average (ARIMA) models in water-level modeling. Results showed approximately similar precision to that of NN models; the same results have been reported by Chattopadhyay and Chattopadhyay (2010). The main distinction between the NN and ARIMA models is the required level of user input (human expertise) and model-building speed, with NN model building reported as being faster than ARIMA model building.…”
supporting
confidence: 78%
“…In this context, the average surface temperature of our planet is mainly controlled by its albedo and the atmospheric greenhouse effect (Cracknell and Varotsos, 1994, 2007aVarotsos, 2002Varotsos, , 2005aFeretis et al, 2002;Efstathiou et al, 2003; Published by Copernicus Publications on behalf of the European Geosciences Union. Tzanis et al, 2008;Varotsos et al, 2008Varotsos et al, , 2012aChattopadhyay and Chattopadhyay, 2010;Varotsos, 2010, 2013;Xue et al, 2011;de la Fuente et al, 2011). For example, the average Earth surface temperature would be −40 • C if it were frozen entirely and 27 • C if all the ice on its surface were to melt.…”
Section: Introductionmentioning
confidence: 99%